SCIENTIFIC PROVISION OF VETERINARY SECURITY IN THE URAL REGION (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
This paper discusses the main areas of research that determine the strategy of scientific support for veterinary well-being in the Ural region. The problem of producing highquality and safe livestock products poses the challenge for veterinary medicine of improving scientific approaches to the formation of an animal health preservation system in the face of external biological threats, industrial pollution of agricultural territories, and the emergence of new transboundary animal diseases. The development of a methodology for predicting, diagnosing, preventing and conducting recreational activities should be based on fundamental knowledge about the molecular genetic characteristics of pathogens, the characteristics of the antigenic landscape, and the state of the immune and metabolic status of animals
Keywords: veterinary safety, livestock products, animal population health, epizootic situation, Ural Federal District, Sverdlovsk region